An Australian-Based View on Reconstructing Copyright Licensing Laws - Cunningham, Robert; Papadopoulos, Marinos; Koutras, Nikos (Springer, 2023)
In the new digital landscape, contemporary issues such as the need to promote online creativity, support digital live streaming, and develop effective computer hardware should be addressed by the copyright licensing scheme. The purpose of the paper is to consider the effectiveness of the copyright licensing scheme in Part IVA of Copyright Act 1968 (Cth) (‘the Act’) and analyse how it can be strengthened to support creativity and digital exchange. The first paper part discusses about justifications for open access, its desirability as a publishing model and lessons drawn from European institutions where efficient implementation of open access is applicable. Hence, such lessons should be considered in a future inquiry from the Australian Law Reform Commission and become part of The Future of Law Reform inquiry (2020). The second paper part considers the institutional perspective by examining specific Australian institutions and argues that ‘reconstruction’ of copyright licencing laws, will further access opportunities, and enhance scientific communication, in Australia. All in all, reconsideration of the final report on Intellectual Property Arrangements Inquiry issued from the Australian Productivity Commission (2016) potentially can lead to gradual integration of an open access provision in ‘the Act’, which will enhance copyright licencing laws.